Managing resources and information : a competence approach to supervisory management (Blackwell Business, 1998)
Understanding businesses. Keeping track of the money. Planning and controlling the money. Costs and costing. How are we doing? Compensation and payment systems. The external environment. The need for information. Using numbers...